PENGARUH PERSEPSI KUALITAS, CITRA MEREK, DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK MASKER WAJAH CAMILLE - Anindy Yovitha (2022)
This research is using quantitative descriptive method about purchasing decisions of Camille's face mask product. The purpose of this research is to analyze and prove the alleged influence of perceived quality, brand image, and electronic word of mouth on purchasing decisions in the use of Camille's product. The population in this research are consumers who has been purchasing Camille's face mask products in the Jabodetabek Area. The data collection used in this research is by distributing a questionnaire with the form named google form by online due to the pandemic conditions. The number of samples on this research is 100 respondents with purposive sampling method. The data analysis technique used is descriptive and inferential analysis using the Smart Partal Least Square (PLS) version 3.0 analysis tool. The results of this data processing indicate that variable (1) perception of quality has a significant effect with 36,8% on purchasing decisions, variable (2) brand image has a significant effect with 27,5% on purchasing decisions, and variable (3) electronic word of mouth has a significant effec with 31,5% on purchasing decisions. This research also shows that the result of R Square Adjusted is 0.800, where are perceived quality, brand image, and electronic word of mouth variables have an influence of 80% on purchasing decisions and 20% are influenced by other variables, such as price, product quality, and lifestyle to accomplish this research.